Discrete bulk sediment properties data from Mercer Subglacial Lake - Skidmore, Mark; Venturelli, Ryan A; Dore, John; Campbell, Timothy; Hawkings, Jon; Tranter, Martyn; Science Team, SALSA; Michaud, Alexander (IEDA: US Antarctic Program Data Center, 2023)
This dataset contains bulk sediment properties measurements from cores collected from Mercer Subglacial Lake by the SALSA project. Included are: physical properties (bulk density, mass water content, porosity, shear strength, particle size distribution, and mineralogy); carbon (inorganic and organic); iron (ascorbate- and dithionite-extractable); and sulfur (acid-volatile and chromium-reducible).